Near- and Far-Surround Suppression in Human Motion Discrimination - Wang, Huan; Wang, Zhengchun; Zhou, Yifeng; Tzvetanov, Tzvetomir (Frontiers in Neuroscience, 2018)
The spatial context has strong effects on visual processing. Psychophysics and modelling studies have provided evidence that the surround context can systematically modulate the perception of center stimuli. For motion direction, these center-surround interactions are considered to come from spatio-directional interactions between direction of motion tuned neurons, which are attributed to the middle temporal (MT) area. Here, we investigated through psychophysics experiments on human subjects changes with spatial separation in center-surround inhibition and motion direction interactions. Center-surround motion repulsion effects were measured under near- and far-surround conditions. Using a simple physiological model of the repulsion effect we extracted theoretical population parameters of surround inhibition strength and tuning widths with spatial distance. All 11 subjects showed clear motion repulsion effects under the near-surround condition, while only 10 subjects showed clear motion repulsion effects under the far-surround condition. The model predicted human performance well. Surround inhibition under the near-surround condition was significantly stronger than that under the far-surround condition, and the tuning widths were smaller under the near-surround condition. These results demonstrate that spatial separation can both modulate the surround inhibition strength and surround to center tuning width.